Optical Properties and Morphological Study of New Films Derived From Poly(Vinyl Chloride)-Phenyl Phrine HCl Acid Complexes - Zageer, Dheaa; Ibraheem, Hanan; Hasan, Ali; Yousif, Emad; Al-Taa'y, Wasan (Al-Nahrain Journal of Science, 2018)
The present study focused on modification of the optical properties of PVC films Phenyle Phrine HCl Acid complexes. Poly(vinyl chloride) (PVC) react with Phenyle Phrine HCl Acid (L) in THF to form the PVC‐L compound. PVC‐L has further been reacted with different metal's ions to form PVC‐L‐MII complexes. The structure of these complexes has been characterized by FT‐IR and UV‐Vis spectrophotometry. The optical data analyzed and interpreted in terms of the theory of phonon assisted direct electronic transitions. According to energy gap data, the conductivity of PVC and the complexes were obtained. From the microscopic image analysis, the relations between morphology and optical properties were explained.